Pelatihan Penggunaan Multimedia Flipbook dalam Peningkatan Soft Skill bagi Mahasiswa Universitas Halu Oleo - Ningtyas, Rita Ayu; Sultrayansa, Sultrayansa; Ulfa, Nur Isnaini; Sriwangi, Sriwangi; Lestari, Dian Trianita; Taufik, Taufik (Civitas Consecratio: Journal of Community Service and Empowerment, 2024)
Multimedia Flipbooks enable students to learn course materials visually, which can help with comprehension and memory. The multimedia flipbook format, which resembles a traditional printed book, adds interest and interactivity to information presentations. Digital flipbooks are accessible through digital devices such as laptops, tablets, and smartphones, allowing students to read and study materials at any time and from any location. Training in the use of multimedia flipbooks aims to improve students’ ability to innovate and be creative by leveraging digital technology. The community service method used in this training is to provide students with information on tips and tricks, as well as the stages of using multimedia flipbooks. The results of the multimedia flipbook training for Halu Oleo University students show that students can gain a comprehensive understanding of flipbooks in terms of their concept, features, and potential as a digital presentation format. Students can also differentiate flipbooks from other digital book formats and understand their benefits. Students can create a flipbook that combines text, images, videos, and animations. Students who complete this training are capable of creating interactive and responsive flipbooks using HTML, CSS, and JavaScript. Overall, flipbooks can improve students’ comprehension, learning efficiency, and engagement in the learning process. This will undoubtedly have a positive impact on student learning and how technology is used to address industry challenges in the future.